The moonstone - Collins, Wilkie, 1824-1889 (Oxford world's classics (Oxford University Press), 1999)
John Sutherland provides a fascinating introduction to a new edition of what T.S. Eliot called 'the first and greatest of all English detective novels'. - ;'the first and greatest of English detective novels' T.S. Eliot A fabulous yellow diamond becomes the dangerous inheritance of Rachel Verinder. Outside her Yorkshire country house watch the Hindu priests who have waited for many years to reclaim their ancient talisman, looted from the holy city of Somnauth. When the Moonstone disappears the case looks simple, but in mid-Victorian England no one is what they seem, and nothing can be taken for.